HISTIOCYTOSIS X: CLINICAL OBSERVATIONS - E. Y. Ponomareva; A. P. Rebrov; E. E. Archangelskaja; A. A. Roshchina; R. N. Steshenko; A. S. Bukia; N. V. Dvornikova; N. N. Moskaleva (Klinicist)
Two clinical cases of pulmonary Langerhans cell histiocytosis X have been analyzed demonstrating lung and other inner organ pathology, common clinical and X-ray features but different life prognosis.